الدراسة الأسلوبية: تحليل أسلوب السخرية والتهكم والهجاء في مسلسل بهلول أعقل المجانين الجزء الأول - Rahmat Zatnika, Aziz (Journal of Arabic Language and Literature (ALLAIS), 2023)
After 2022, people's trends will have changed with the times. Watching films will become a new lifestyle in our society. Films have a diverse impact on society and are a means of conveying messages that are easily accepted, but understanding a film also requires sufficient insight. Stylistics is a way of greeting something to achieve what is intended; understanding stylistics will support understanding when watching movies. The first season of "Bahlul A'qalul Majanin" is a film that is full of satirical language; therefore, it is necessary to understand the satirical stylistics to understand this and similar films better. This research is descriptive qualitative research using text (content) analysis methods with data in the form of conversations and speech in the first season of the "Bahlul A'qalul Majanin" series. This research data was collected by observation (watching live) and then listening to the conversations and speeches in this series, after which the existing data was recorded. This study found that satire has several patterns for each type of satirical style that can be understood and seen quite clearly, from the foundation, purpose, and expression to the choice of words and sentences. The study also found the following number of satirical styles: 40 for irony, 17 for sarcasm, and 17 for satire.